Voltammetry as a probe of displacement. - Rees, N; Compton, R (2010)
Dynamic electrochemistry has been often viewed from outside the field as primarily a means to determine kinetic and thermodynamic information about redox-active species in solution. However, in recent years electrochemical applications have become increasingly diverse. In this brief review, we survey the use of voltammetry as a probe of distance, starting with scanning electrochemical microscopy (SECM) and arriving at the present day with characterisation of moving particles and nanoscale measurements.